Kinin B1 receptor blockade attenuates hepatic fibrosis and portal hypertension in chronic liver diseases in mice - Dileep Reddy Rampa; Huiying Feng; Sivakumar Allur-Subramaniyan; Kwanseob Shim; Anton Pekcec; Dongwon Lee; Henri Doods; Dongmei Wu (Journal of Translational Medicine, 2022)
Abstract Background and aims Kinin B1 receptors (B1Rs) are implicated in the pathogenesis of fibrosis. This study examined the anti-fibrotic effects of B1R blockade with BI 113823 in two established mouse models of hepatic fibrosis induced by intraperitoneal carbon tetrachloride (CCl4) injection or bile duct ligation (BDL). The mechanisms underlying the protection afforded by B1R inhibition were examined using human peripheral blood cells and LX2 human hepatic stellate cells (HSCs). Methods Fibrotic liver diseases were induced in mice by intraperitoneal carbon tetrachloride (CCl4) injection for 6 weeks, and by bile duct ligation (BDL) for 3 weeks, respectively. Mice received daily treatment of vehicle or BI 113823 (B1R antagonist) from onset of the experiment until the end of the study. Results B1Rs were strongly induced in fibrotic mouse liver. BI 113823 significantly attenuated liver fibrosis and portal hypertension (PH), and improved survival in both CCl4 and BDL mice. BI 113823 significantly reduced the expression of fibrotic proteins α-SMA, collagens 1, 3, 4, and profibrotic growth factors PDGF, TGFβ, CTGF, VEGF, proliferating cell nuclear antigen; and reduced hepatic Akt phosphorylation in CCl4- and BDL-induced liver fibrosis. BI 113823 also reduced expression of Cytokines IL-1, IL-6; chemokines MCP-1, MCP-3 and infiltration of inflammatory cells; and inhibited human monocyte and neutrophil activation, transmigration, TNF-α & MPO production in vitro. BI 113823 inhibited TGF-β and B1R agonist-stimulated human-HSC activation, contraction, proliferation, migration and fibrosis protein expression, and inhibited activation of PI3K/Akt signalling pathway. Conclusions B1Rs merits consideration as a novel therapeutic target for chronic liver fibrosis and PH.